Persepsi Masyarakat Terhadap Perubahan Rupa Elemen Ruang Publik Pada Koridor Jalan Nangka Utara Denpasar - Suryada, I Gusti Agung Bagus (Jurnal Arsitektur Universitas Udayana; Vol 13 No 01 (2025): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v13i01.124442, 2025)
Sidewalks, as facilities for pedestrians, have specific requirements. Nangka Utara Street, located on the outskirts of Denpasar City, has undergone changes in the appearance of its sidewalks in several segments. These changes not only have physical impacts but also non-physical effects, such as the area's image. The image of an area is determined by the average perceptions of its community, making it essential to understand how the public perceives the changes in sidewalk appearance. This study employs a qualitative approach. Data collection was conducted through field observations and interviews using questionnaires. Data analysis was performed using literature review methods. The findings indicate that public perception of changes in shape, texture, and color of the sidewalks diminishes their aesthetic appeal. Continuity and the perception of the space as a public area decrease when color changes occur. Keywords: perception, community, changes, public space, sidewalk.